Cognitive radio networks - Jiang, Tao; Wang, Zhiqiang; Cao, Yang (London CRC PRESS, 2015)
Resource allocation is an important issue in wireless communication networks. In recent decades, cognitive radio-based networks have garnered increased attention and have been well studied to overcome the problem of spectrum scarcity in future wireless communications systems. Many new challenges in resource allocation appear in cognitive radio-based networks. This book focuses on effective resource allocation solutions in several important cognitive radio-based networks, including opportunistic spectrum access networks, cooperative sensing networks, cellular networks, high-speed vehicle networks, and smart grids.
1. Introduction -- 2. Transmission slot allocation in an opportunistic spectrum access network -- 3. Sensing node allocation in a cognitive radio network with cooperative sensing -- 4. Transmission power allocation in a cognitive radio network -- 5. White space allocation in a cognitive radio-based high-speed vehicle network -- 6. Sensing channel allocation in a cognitive radio network for a smart grid.
Keywords: Cognitive radio networks; Radio resource management (Wireless communications); Technology